Skin Microbiome in Small- and Large-plaque Parapsoriasis - Alexander Salava; Pedro Pereira; Velma Aho; Liisa Väkevä; Lars Paulin; Petri Auvinen; Annamari Ranki; Antti Lauerma (Medical Journals Sweden, 2017)
Staphylococcal enterotoxins have been shown to promote lymphoma-associated immune dysregulation. This study examined changes in the skin microbiome of parapsoriasis compared with intact skin. Swab microbiome specimens were taken of the parapsoriasis lesions of 13 patients. Control samples were taken from contralateral healthy sides of the body. Microbiotas were characterized by sequencing the V1-V3 region of the 16S ribosomal RNA bacterial genes on the Illumina MiSeq platform. The most common genera in the microbiome data were Propionibacterium (27.13%), Corynebacterium (21.20%) and Staphylococcus (4.63%). Out of the Staphylococcus sequences, 39.6% represented S. epidermidis, with the rest including S. hominis, S. capitis and unidentified species. No significant differences were observed between the patients' parapsoriasis and contralateral healthy skin or between large- and small-plaque parapsoriasis. Notable interpersonal variation was demonstrated. These results suggest that parapsoriasis is not associated with significant alterations in the cutaneous bacterial microbiome.